Analisis Strategi Branding Public Relations untuk Meningkatkan Brand Awareness “Janji Jiwa” - Fitria Salsabilla; Christian Wiradendi Wolor; Marsofiyati Marsofiyati (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
This research aims to analyze the branding strategy through the Public Relations (PR) approach implemented by Janji Jiwa in increasing brand awareness in the local Indonesian coffee market. PR strategies have an important role in strengthening brand identity, creating emotional connections with audiences, and building customer loyalty. This research method uses a descriptive qualitative approach by collecting data through literature studies, interviews, and analysis of social media and the Janji Jiwa PR campaign. The research results show that Janji Jiwa utilizes consistent brand communication, strategic collaboration with influencers and communities, as well as creative campaigns based on authentic stories to create consumer engagement. Additionally, the integration of digital and offline activities, such as product launches, interactive content, and community events, successfully increases brand visibility and appeal. Continuous monitoring and evaluation of market trends and the effectiveness of PR campaigns is also key to the success of this branding strategy. This research provides practical insights for business people in developing PR strategies to build brand awareness in competitive industries.